The Influence of Service Quality on SINTA Acceptance Using the TAM Method: A Case Study of Lecturers at X University - Elnusa, Diadara Shalom; Padmawidjaja, Liestya; Salim, Ika Raharja (Jurnal Entrepreneur dan Entrepreneurship, 2025)
LPPM X University is responsible for managing administration and providing research and community service data for both internal and external purposes. One of the databases managed by LPPM X University is SINTA. However, an evaluation has yet to be conducted to assess the acceptance of X University lecturers regarding the use of SINTA. This research aims to analyze the extent of X University lecturers’ acceptance of SINTA. It also aims to examine the mediating effect of service quality on the acceptance of SINTA. The study employs the Technology Acceptance Model (TAM) with service quality as a mediating variable. The research method used is quantitative, with data collection using questionnaires and data processing using SMARTPLS 4. All variables meet the validity criteria and fulfill the construct reliability based on the collected data. The results of this study show that service quality significantly impacts the acceptance of SINTA by lecturers.